Podología preventiva: niños descalzos igual a niños más inteligentes - Gentil García, Isabel (Revista Internacional de Ciencias Podológicas, 2007)
At present there is a trend to wear the children precocious. There are shoes to wear the infant for prewalking and footwear for the crawling. In this article the author tries to offer scientific arguments to justify the need to leave barefoot the feet of the not walking babies. The methodology used has been the analysis and critical reading of different bibliographical sources in relation to the development of the psicomotivity in the child, as weel as, neurology textbook and the principal Theories on the development of the intelligence in the child. We think that the physical movement and the sensory stimulus of the baby through the barefoot feet is a factor of acceleration of the growth, the propioceptive development and the intellectual development of the child.